Gas-liquid simulation of an airlift bubble column reactor - Zulkifly, Nurul Shahida (2015)
Airlift bubble column reactors are finding increasing application on industries such as bioprocess industries. The gas-liquid of two-phase fluid flow system has been carried out to investigate the hydrodynamics parameter. An Eulerian-Eulerian approach was used to model air as the dispersed phase within a continuous phase of water using the commercial software ANSYS FLUENT 15.0. The turbulence in the gas-liquid simulation is described by using the K-Epsilon model, RNG K-Epsilon model and K-Omega model. This process occurs under atmospheric pressure. The volume fraction of model is described the behavior of bubble which is represented by the parameters of gas hold up, contact surface area and gas superficial velocity. The simulation was verified by comparing the three different model results. Result shows the contact surface area increasing with behavior of bubble and gas hold up increases with increasing superficial gas velocity. The highest value obtained from K-Omega model which represented of contact surface area, gas hold up and superficial gas velocity of 0.00082m2, 0.3% and 0.0107 m/s respectively. The range of superficial gas velocity is 0.000815426 m/s to 0.010743066 m/s. These produced results reveal that ANSYS FLUENT, K-Omega model have excellent potential to simulate the two-phase flow system.